HUNIAN DAN FASILITAS REKREASI PESISIR LAMBOLO - Kevin Adriel; Sutarki Sutisna (Jurnal Sains, Teknologi, Urban, Perancangan, Arsitektur (Stupa), 2021)
The ecological crisis is a global challenge for mankind at the beginning of the 21st century which has not been resolved until now. Governments and people around the world are very concerned about the worsening environmental conditions. The crisis destroys the entire natural ecology of the earth which affects the entire ecosystem. Taking Natural Resources irresponsibly will result in damage to the surrounding environment. All living things depend on the earth's energy, but if it is handled incorrectly, the environment will be damaged due to careless extraction of natural resources. One problem arose due to nickel mining activities by a nickel smelter in North Morowali, Central Sulawesi, which resulted in environmental damage, especially in Hamlet V Lambolo, which is adjacent to the coast of Tomori Bay. The buildings that are built must not damage the environment, and the damaged environment must be repaired according to the aspects of the Sustainable Development Goals. The purpose of this plan is to produce a design by rehabilitating the area so that the problems there can be solved by problem solving programs and existing social recreation programs with ecological architectural designs. Keywords: Architectural Design; Ecological Crisis, Environmental Damage; Natural Resources, Sustainable Development GoalsAbstrak Krisis ekologi merupakan tantangan global umat manusia pada awal abad 21 yang sampai sekarang belum terselesaikan. Pemerintah dan masyarakat di seluruh dunia sangat prihatin dengan kondisi lingkungan yang makin lama kian memburuk. Krisis tersebut merusak seluruh ekologi alam di bumi yang berdampak pada seluruh ekosistem. Pengambilan Sumber Daya Alam (SDA) dengan tidak bertanggung jawab akan berakibat pada kerusakan lingkungan sekitar. Semua makhluk hidup sangat bergantung pada energi bumi, namun jika penanganannya salah maka lingkungan akan rusak akibat pengambilan SDA secara ceroboh.Satu masalah muncul akibat aktivitas penambangan nikel oleh salah satu smelter nikel di Morowali Utara, Sulawesi Tengah yang berdampak pada kerusakan lingkungan terutama di Dusun V Lambolo yang berdekatan dengan pesisir Teluk Tomori.   Bangunan yang terbangun harus tidak boleh merusak lingkungan, dan lingkungan yang rusak harus dibenahi menganut aspek-aspek dari Suistainable Development Goals. Tujuan perencanaan ini adalah untuk menghasilkan rancangan dengan me-rehabilitasi kawasan tersebut supaya masalah-masalah disana dapat terselesaikan dengan program penyelesaian masalah serta program rekreasi sosial eksisting dengan desain arsitektur ekologi.